Public Health Education through Labeling on Medicinal and Family Plants (TOGA) in Pagarawan Village - Nyayu Siti Khodijah; Faradiba Faradiba; Minawati Minawati; Ratna Santi; Ririn Aquarina; Winda Wahyuni (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2022)
The development of technology has experienced many advances, one of which is the processing of chemical compounds into drugs that can cure various diseases. However, the use of chemical drugs is considered to have side effects on health so that people switch to herbal medicines that are more natural and have minimal side effects such as the use of family medicinal plants (TOGA). Pagarawan Village is one of the villages that has great potential to be developed as a family medicinal plant (TOGA) producing village. The main problem faced by the community of Pagarawan Village, Merawang Subdistrict, Bangka Regency is the lack of knowledge about the types of plants that have medicinal properties. Therefore, it is necessary to provide education through the introduction and utilization of home yards for TOGA and TOGA Labeling. Family medicinal plants (TOGA) are plants that have benefits and properties that are good for health and are planted in the yard to meet family medicinal needs. The purpose of this activity is to provide education and understanding to the community about the utilization of yard land as a place for planting TOGA in order to provide family herbal medicine. This activity was carried out on August 16, 2021 to October 25, 2021, located in Pagarawan Village, Merawang District, Bangka Regency. This community service activity involves various parties including Pagarawan Village Office Employees, Merawang District, Bangka Regency, the community and KKN students. The activity began with the utilization of an empty yard located behind the Pagarawan Village Office. This is because the Village Office is one of the community service centers, so it is expected to be an example for the local community. The availability of TOGA in Pagarawan Village is expected to help the community in utilizing TOGA for health.